Reading aloud practices by ESL teachers / Nor Aafina Mohd. Zamil - Mohd. Zamil, Nor Aafina (2010)
The purpose of this study is to investigate the extent and frequency of reading aloud practices by teachers in ESL classrooms. Specifically, this study is conducted to investigate the frequency of reading aloud practices by teachers in ESL classrooms, the reasons teachers give for reading aloud and not reading aloud during lesson, the types of texts that teachers use for reading aloud activities and how teachers extend the read aloud activity. The data for this study was via the distribution of questionnaires to a sample of 50 respondents. The findings of this study reveal that a majority of teachers do practice reading aloud to their students during lessons because they want to model fluent reading and model word and vocabulary pronunciation. Most of them use literature anthologies as their preferred texts. Other text choices include; poetry books, non-fictional biographies and chapter books. On the other hand, teachers who say they do not read aloud to their students claim that there is not enough time in the day for this activity and that they do not think that reading aloud is an important instructional practice.